2018
DOI: 10.3390/s18092975
|View full text |Cite
|
Sign up to set email alerts
|

Translational Acceleration, Rotational Speed, and Joint Angle of Patients Related to Correct/Incorrect Methods of Transfer Skills by Nurses

Abstract: Currently, due to shortages in the nursing faculty and low access to actual patients, it is difficult for students to receive feedback from teachers and practice with actual patients to obtain clinic experience. Thus, both evaluation systems and simulated patients have become urgent requirements. Accordingly, this study proposes a method to evaluate the nurse’s transfer skill through observation from the patient. After verifying the proposed method, it will be integrated with a robotic patient as a future work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…Results show that the parameter values measured by the robot patient indicate significant differences in nine of the thirteen incorrect methods of the transfer skill in terms of the effects on the robot patient. Moreover, a comparison with [35] showed that, during most steps, the effects on the robot patient were identical to the effects on the SPs portrayed by nursing teachers.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Results show that the parameter values measured by the robot patient indicate significant differences in nine of the thirteen incorrect methods of the transfer skill in terms of the effects on the robot patient. Moreover, a comparison with [35] showed that, during most steps, the effects on the robot patient were identical to the effects on the SPs portrayed by nursing teachers.…”
Section: Introductionmentioning
confidence: 74%
“…To evaluate the transfer skill, Lin et al [35] proposed a checklist to transfer a patient suffering from weak lower limbs. The checklist includes both correct and incorrect methods, which were determined based on discussions with nursing teachers and reviews of nursing materials, as presented in Fig.…”
Section: Checklist For Patient Transfer Skillmentioning
confidence: 99%
See 3 more Smart Citations